2021
DOI: 10.3390/pharmaceutics13020132
|View full text |Cite
|
Sign up to set email alerts
|

Improving Breviscapine Oral Bioavailability by Preparing Nanosuspensions, Liposomes and Phospholipid Complexes

Abstract: Breviscapine (BVP), a flavonoid compound, is widely used in the treatment of cardiovascular and cerebrovascular diseases; however, the low oral bioavailability and short half-life properties limit its application. The aim of this study was to investigate the three preparations for improving its oral bioavailability: nanosuspensions (BVP-NS), liposomes (BVP-LP) and phospholipid complexes (BVP-PLC). In vitro and in vivo results suggested that these three could all significantly improved the cumulative released a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…6. Liposomes were observed to be spherical and oval with a smooth surface similar to images previously reported for astaxanthin-loaded liposomes 15,27) , cisplatin-loaded liposomes 28) , sea cucumber-derived saponin liposomes 1) , and breviscapine-loaded liposomes 29) . The particle size of liposomes was approximately 100-150 nm in size, which was in good agreement with the mean size particle measured by Zetasizer (Table 1) .…”
Section: Liposome Morphologysupporting
confidence: 84%
See 1 more Smart Citation
“…6. Liposomes were observed to be spherical and oval with a smooth surface similar to images previously reported for astaxanthin-loaded liposomes 15,27) , cisplatin-loaded liposomes 28) , sea cucumber-derived saponin liposomes 1) , and breviscapine-loaded liposomes 29) . The particle size of liposomes was approximately 100-150 nm in size, which was in good agreement with the mean size particle measured by Zetasizer (Table 1) .…”
Section: Liposome Morphologysupporting
confidence: 84%
“…The release of astaxanthin in mice serum of astaxanthin-loaded liposomes was prolonged because of slow disintegration and solid structure of lipid carriers according to previous reports 33,34) . Moreover, only liposomes that exist in the gastrointestinal tract and be able to enter into the mucus layers can reach the intestinal epithelia and can be absorbed together with the loaded materials 29,35) , suggesting that dietary astaxanthin in liposome form could significantly improve the bioavailability.…”
Section: In Vivo Digestion and Absorptionmentioning
confidence: 99%
“…When the ratio was increased to 1:4, the phytosomes were larger. Song et al, prepared breviscapine phospholipid complexes at different drug-lipid mass ratios (1:1, 1:2, 1:3), and the particle size tended to increase with increasing lipid content [ 55 ]. One possible explanation for this result was that excessive amounts of phospholipid molecules contributed to aggregation, leading to a larger size.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Hu et al ( 2021 ) reported that cellulose capsules loaded with tangeretin reported a plasma concentration 22 times higher than the unencapsulated flavonoid solution when administered to a rat model. Song et al ( 2021 ) reported that breviscapine‐loaded capsules administered to a Sprague–Dawley rat model reported values of C max 4.4 and 2.9 times higher than the non‐encapsulated flavonoid. Likewise, the values of the area under the capsules' concentration curve were at least 2.5 times higher than that reported by the non‐encapsulated suspension of this flavonoid.…”
Section: Bioavailability Of Flavonoids Prospects For the Development ...mentioning
confidence: 99%